Comparison of Pressure Support versus T-Piece Trial for Weaning from Mechanical Ventilation: Postoperative Ventilator Weaning - Bashir, Sheeza; Rashid, Muhammad; Qureshi, Ayesha; Bhatti, Asma; Munir, Fariha; Ahmad, Mian Sajjad; Sarwar, Muhammad Usman (Pakistan Journal of Health Sciences, 2025)
Post-operative patients are particularly vulnerable to hazardous effects of prolonged ventilation owing to their limited reserves, catabolic state and acute injury related to surgical incision and dissection. Thus, early weaning protocols are required for better outcome in this population. Objective: To compare PSV versus T-Piece trial for weaning from Mechanical Ventilation. Methods: The quasi experimental study was conducted at ICU of Mayo Hospital Lahore from 28-05-2021 to 28-11-2021. Total 60 patients undergoing elective post-operative mechanical ventilation were selected after taking written informed consent. Patients were divided in two groups, Group A: Pressure support ventilation and Group B: T piece ventilation. Frequency and percentage of successful extubation were recorded in both groups. Data were analysed with SPSS version 26.0. Frequency of successful extubation was compared using chi square test taking p-value ≤0.05 as significant. Results: In Group A, 93.33% (n=28) of patients had successful extubation, while only 66.66% (n=20) patients in Group B had successful extubation, p-value=0.009. Conclusion: This study indicated that PSV results in successful extubation and liberation from mechanical ventilation than T piece trial.